Design for elderly usability: case study on clinic management system / Mohamed Yaseen Shaik Dawood - Shaik Dawood, Mohamed Yaseen (2012)
Using a computer is commonly experienced as a problem amongst elderly people. The objective of this study is to identify concept and feature for elderly usability, design clinic management system using identified concept, and conduct usability on the proposed system. Firstly, an elaborate description of the user group and the problem is given. The user group and problem have been researched by studying literature, observing the user group at work. Based on these results, prototype design been designed implementing suggested improvements for the found problems. These features have been tested and evaluated by conducting usability testing and interviews with identified users. Finally, the report is concluded base on result, research limitation and suggestion for future work.